TRANSFORMASI KONFLIK DENGAN PENDEKATAN MEDIASI PADA KONFLIK BUTON - AAN SURYATWAN; Adis Imam Munandar (Journal Publicuho, 2020)
Horizontal conflict in the form of ethnicity and religion still occurs today as inter-ethnict conflict between Gunung Jaya and Sampoabalo villages. In addition to the litigation process, non-litigation steps such as mediation in conflict resolution can play an important role. This study aims to describe how the process of conflict transformation with the mediation approach to conflict that occurs in the Buton district. This study uses a descriptive qualitative method through literature studies and observations on the events of Buton and its historical social conflicts. The result of the study illustrates that conflict transformation with a mediation approach is a very effective solution to the conflicts that occur in Buton between Gunung Jaya and Sampoabalo villages by looking at the initial process to the end of conflict resolution efforts. The mediation steps in Buton conflict resolution efforts include are the Introductions stage, storytelling stage, problem solving stage and agreement stage.